2019
DOI: 10.1016/j.cma.2019.03.058
|View full text |Cite
|
Sign up to set email alerts
|

A phase-field description for pressurized and non-isothermal propagating fractures

Abstract: In this work, we extend a phase-field approach for pressurized fractures to non-isothermal settings. Specifically, the pressure and the temperature are given quantities and the emphasis is on the correct modeling of the interface laws between a porous medium and the fracture. The resulting model is augmented with thermodynamical arguments and then analyzed from a mechanical perspective. The numerical solution is based on a robust semi-smooth Newton approach in which the linear equation systems are solved with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…In the case of elastic cracks, it can be shown that the phase field satisfies 0 ≤ d ≤ 1. When additional physics are included for instance a fluid inside the fracture [74] or non-isothermal effects [79], the energy functional must be modified to cope with negative values of d. Hence in order to allow for future extensions, we work in the remainder of this paper with d + rather than d. A detailed discussion is provided in [74][Section 3].…”
Section: Phase-field Approximation Of Anisotropic Crack Topologiesmentioning
confidence: 99%
“…In the case of elastic cracks, it can be shown that the phase field satisfies 0 ≤ d ≤ 1. When additional physics are included for instance a fluid inside the fracture [74] or non-isothermal effects [79], the energy functional must be modified to cope with negative values of d. Hence in order to allow for future extensions, we work in the remainder of this paper with d + rather than d. A detailed discussion is provided in [74][Section 3].…”
Section: Phase-field Approximation Of Anisotropic Crack Topologiesmentioning
confidence: 99%
“…The following three-dimensional research studies using PF are available: formation and growth of echelon cracks [164], pressure vessel simulation [158], single-edge notched shear test [162], cube with rigid spherical inclusion under tension [157], Kalthoff Winkler experiment [157], bolted plate compared against experimental results [161], simple shear tests of thoracic aorta with anisotropic failure compared against experimental results [163], random nucleation sites [159], L-shaped specimen [160,233], tension test of cube with spherical inclusion [112], bending of Hopkinson bar [363], and Sneddon/Lowengrub benchmark [146,217,237], and non-isothermal pressurized fractures [364].…”
Section: Challengesmentioning
confidence: 99%
“…The computational costs can be high, specifically when an appropriate estimation is required inside multi-physics frameworks, see e.g. [ 3 , 26 28 ]. Using Bayesian inversion, we strive to solve such problems with a coarser mesh and fit the parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, sufficiently small length-scales are computationally demanding. To date, the focus in such cases was on local mesh adaptivity and parallel computing in order to reduce the computational cost significantly; see for instance [3][4][5][6][7][8][9][10][11]. Another recent approach is a global-local technique in which parts of the domain are solved with a simplified approach [12,13] that also aims to reduce the computational cost.…”
mentioning
confidence: 99%